Temporarily Transfixation of the distal interphalangeal Joint in Mallet fingers - Suffa, Nadine; Merkel, Pauline; Horch, Raymund E.; Arkudas, Andreas; Ludolph, Ingo; Stumpfe, Maximilian Christoph (Handchirurgie, Mikrochirurgie, Plastische Chirurgie, 2021)
Zusammenfassung
CRIS-Team WoS Importer:2021-10-08